O remix midiático das séries de televisão Cowboy Bebop e Samurai Champloo - Almeida, Roberta Regalcce de (2010)
This dissertation aims to analyze two Japanese animation series for TV, Cowboy Bebop (1998) and Samurai Champloo (2004) by Shinichiro Watanabe. The both series are emblematic by using a remix of the traditional and the modern, the Japanese culture and the West, generating unusual metamorphoses and creating multiple interfaces between various contexts and media experience (television, movies, games, manga etc.). The research analyzes the strategies of remix, typical of so-called post-production, on the dynamics of selection and appropriation of media products and objects of consumption, and their reuse in other forms and contexts, redefining them, as a focus of epistemological critical analysis. The goal is to analyze if the author s remix can be considered in fact, one author. In support of discussion, the research selected authors who have dedicated themselves to track the origins, functions and uses of the remix, and the modulations of this process in pop culture throughout the twentieth century as Lev Manovich (2005), Eduardo Navas (2008), Nicolas Bourriaud (2009) and Lucia Santaella (2007). Moreover, the theory corpomídia (Greiner and Katz 2005) explains how to avoid the deterministic analysis that consider the work and the author as objects and subjects entered by the culture. The analitic methodology for the both series, while remixes of Japanese pop culture, focuses on observing and reporting different sources, indicating their mediation. As media products, the series will finally be recognized as maps or overlapping layers, as the researchers specializing in Japanese pop culture has been discussing in recent years (Looser 2009, Igarashi 2001, Greiner, 1998 and 2000 and Luyten, 2000). The expected result is a reflection that will not invoke the traditional dichotomies between East and West and it is focused on analyzing the media culture, with emphasis on representations of corpomídia that appears as a mark of natural experiments studied